Revitalisasi Pembelajaran Berbasis HOTS Di Abad 21 - Alexandria Sarah Vania; Annisa Sabilla; Aulia Nur Hakim; Varina Handayani Sudrajat; Yohana Romauli Sianturi (CV. Ulil Albab Corp, 2022)
Education is an important pillar in building an advanced and prosperous nation and civilization. All challenges in education must be addressed immediately, such as the challenges in education in Indonesia and other countries caused by the Covid-19 pandemic. These challenges caused Indonesia to experience a setback with learning losses in terms of literacy, numeracy and student character. The solution taken by Indonesia is the restoration of the curriculum. This research is intended to examine the importance of curriculum restoration through the implementation of a sovereign curriculum. The method used in this research is qualitative research with literature study data collection method. The results show that the sovereign curriculum has advantages, including emphasizing character strengthening through project-based learning, mastering literacy and numeracy skills through essential learning and also learning independence through teacher flexibility in carrying out learning. These advantages can overcome the learning loss experienced in Indonesian education. So that the sovereign curriculum is the right curriculum option to be applied because it can restore the condition of Indonesian education.